2022
DOI: 10.1111/1758-2229.13040
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of organic phosphorus recycling by soil bacteria: acquisition, metabolism, and regulation

Abstract: Summary Critical to meeting cellular phosphorus (P) demand, soil bacteria deploy a number of strategies to overcome limitation in inorganic P (Pi) in soils. As a significant contributor to P recycling, soil bacteria secrete extracellular enzymes to degrade organic P (Po) in soils into the readily bioavailable Pi. In addition, several Po compounds can be transported directly via specific transporters and subsequently enter intracellular metabolic pathways. In this review, we highlight the strategies that soil b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 235 publications
(331 reference statements)
2
31
0
Order By: Relevance
“…The 16S rDNA sequencing analysis suggested 73 phytase-producing bacteria isolates grouped into two phyla which consisted of 16 different genera. Proteobacteria (90.41%) was the most dominant, including Pseudomonas, Acinetobacter, Variovorax, Achromobacter, Pantoea, Arthrobacter, etc., and more than 49% (36) of isolates belongs to Pseudomonas, which also confirmed that the γ-Proteobacteria was the main bacterial group producing phytase, as reported by Park et al (2022). In addition, we compared the extracellular phytase activity between genera of Pseudomonas and others to confirm the dominant genus, and the results indicated that isolates of Pseudomonas in the present work had a higher average activity, which could be representative within strains colonized in grass rhizosphere in the soils studied.…”
Section: Discussionsupporting
confidence: 88%
“…The 16S rDNA sequencing analysis suggested 73 phytase-producing bacteria isolates grouped into two phyla which consisted of 16 different genera. Proteobacteria (90.41%) was the most dominant, including Pseudomonas, Acinetobacter, Variovorax, Achromobacter, Pantoea, Arthrobacter, etc., and more than 49% (36) of isolates belongs to Pseudomonas, which also confirmed that the γ-Proteobacteria was the main bacterial group producing phytase, as reported by Park et al (2022). In addition, we compared the extracellular phytase activity between genera of Pseudomonas and others to confirm the dominant genus, and the results indicated that isolates of Pseudomonas in the present work had a higher average activity, which could be representative within strains colonized in grass rhizosphere in the soils studied.…”
Section: Discussionsupporting
confidence: 88%
“…Through functional prediction (using PICRUSt2), 38 genes involved in P transformation were detected ( Park et al, 2022 ). PoR treatment significantly decreased the abundance of the phoU and pst genes, while it significantly increased the abundance of the phoR and phnA genes and genes coding for alkaline phosphatase and C-P lyase ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Maize-soybean intercropping could increase soil P availability through multiple mechanisms including root exudates and proton-induced dissolution of P-containing minerals, increased phosphatase activity, and functional microbe-mediated P i mobilization and P o mineralization ( Hinsinger, 2001 ; Betencourt et al, 2012 ; Amadou et al, 2021 ; Park et al, 2022 ). In this study, rhizospheric OC content significantly increased for both crops under the NB treatment relative to the SB treatment ( Table 2 ), which reflected the accumulation of rhizosphere OC under the NB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For the cycling of P o pools, enzymes serve as one of the major driving factors to mineralize P o into the available P i pool for crop uptake ( Richardson et al, 2009 ; Park et al, 2022 ; Yu et al, 2022 ). Generally, the ALP in soils is considered as microbial origin, while the PDE could be from plant roots and microbes ( Amadou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%